Effects of elastic band resistance training on lower limb strength and balance function in older adults: a systematic review and meta-analysis - Meng, Yunchen; Hu, Yiling; Yang, Wang; Xue, Yaqi; Yang, Sanjun (Frontiers in Sports and Active Living, 2025)
IntroductionThis study systematically evaluated the effectiveness of elastic band resistance training (EBT) in improving lower limb strength and balance function in older adults with different health status.MethodsA comprehensive literature search was conducted across Scopus, EBSCO, Web of Science, PubMed, and Cochrane Library to identify randomized controlled trials (RCTs) published through December 30, 2024. Eligible studies included older adults in which the control group received either no intervention or basic treatment, and the experimental group received EBT in addition to the control protocol.ResultsA total of 25 studies involving 1,318 participants were included. Meta-analysis demonstrated significant improvements in the EBT group compared with controls across multiple outcomes: leg extension test [SMD = 1.01, 95% CI (0.36, 1.66), p = 0.002], chair stand test [SMD = 2.04, 95% CI (0.60, 3.48), p = 0.006], timed up and go test [SMD = –1.41, 95% CI (–2.33, −0.49), p = 0.003] and functional reach test [SMD = 1.63, 95% CI (0.36, 2.90), p = 0.012].ConclusionElastic band resistance training may improve lower limb strength and balance function in older adults with different health conditions. Longer intervention durations may yield greater benefits in strength, while balance improvements can occur with shorter programs. Further high-quality studies are needed to confirm these effects.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251021955, PROSPERO CRD420251021955.